Special Sequences on Generalized Metric Spaces (European Journal of Pure and Applied Mathematics, 2022)
In this article, in a generalized metric space, we will focus on new types of sequences. We introduce three new kinds of Cauchy sequences and study their significance in generalized metric spaces. Also, we give several interesting properties of these sequences.
Keywords: kernel; Bourbaki-Cauchy sequence; pseudo-Cauchy sequence; Bourbaki-complete metric space; weakly complete metric space; asymptotic sequence